Energy storage for power systems - Ter-Gazarian, A. (IET energy engineering series, 2020)
Unregulated distributed energy sources such as solar roofs and windmills and electric vehicle requirements for intermittent battery charging are variable sources either of electricity generation or demand. These sources impose additional intermittent load on conventional electric power systems. As a result thermal power plants whose generation is absolutely essential for any power system are increasingly being used for cycling operations thus increasing greenhouse gas emissions and electricity cost. The use of secondary energy storage might be a solution. Various technologies for storing electric energy are available; besides electrochemical ones such as batteries, there are mechanical, chemical and thermal means, all with their own advantages and disadvantages regarding scale, efficiency, cost, and other parameters. This classic book is a trusted source of information and a comprehensive guide to the various types of secondary storage systems and choice of their types and parameters. It is also an introduction to the multidisciplinary problem of distributed energy storage integration in an electric power system comprising renewable energy sources and electric car battery swap and charging stations. The 3rd edition has been thoroughly revised, expanded and updated. All given data has been updated, and chapters have been added that review different types of renewables and consider the possibilities arising from integrating a combination of different storage technologies into a system. Coverage of distributed energy storage, smart grids, and EV charging has been included and additional examples have been provided.